Is Preoperative Anemia a Prognostic Marker in Patients Who Underwent Pneumonectomy for Non-Small Cell Lung Cancer? - Kılıç, Burcu; Özçıbık Işık, Gizem; Turan, Tolunay; Erşen, Ezel; Kara, H. Volkan; Kaynak, M. Kamil; Turna, Akif (Cerrahpaşa Medical Journal, 2024)
Objective: Pneumonectomy is infrequently selected for lung resections due to the high rate of postoperative complications. Thus, identifying risk factors for complications and predicting potential prognostic factors in patients undergoing pneumonectomy is of great importance. We have already described anemia in preoperative patients as a risk factor for postoperative complications. Our objective was to investigate the impact of anemia on pneumonectomy patients’ postoperative course and reveal any potential prognostic effects. Methods: In total, 118 patients who underwent pneumonectomy between 2001 and 2022 were retrospectively assessed. Clinical data, laboratory data, pulmonary function values, pathological data, and survival data were retrospectively recorded, and this data was divided into 2 groups: preoperative hemoglobin values (group 1 anemic: 51 patients) and normal hemogram values (group 2 normal: 67 patients). Univariate and multivariate analyses were conducted. Results: The evaluation of the development of complications in patients who underwent pneumonectomy did not reveal any clinical condition to be a risk factor, apart from anemia. The Charlson comorbidity risk index, pulmonary risk index, and cardiac risk index were not risk factors for complications in pneumonectomy patients (P = .324, P = .192, P = .727, respectively). A significant difference in survival rates was observed between the groups with and without anemia (P = .028). Conclusion: Anaemia was identified as the only prognostic factor in patients who underwent pneumonectomy. Clinical significance must be taken into account to ensure survival benefits. Cite this article as: Kılıç B, Işık GÖ, Turan T, et al. Is preoperative anemia a prognostic marker in patients who underwent pneumonectomy for non-small cell lung cancer? Cerrahpaşa Med J. 2024;48(2):152-158.